O neki zvezi med Riemannovo funkcijo zeta in praštevili - Simonič, Aleksander (Obzornik za matematiko in fiziko, 2014)
In the article we demonstrate how to express the series $\sum_p f(p^{-s})$ in terms of Riemann zeta function, where $f$ is a holomorphic function and summation goes through primes. Next we study analytic properties of such functions.
Keywords: matematika; mathematics; funkcijske vrste; praštevilska funkcija zeta; Möbiusova funkcija; holomorfne funkcije; problem analitičnega nadaljevanja